Evaluating metronidazole as a novel, safe CYP2A6 phenotyping probe in healthy adults. Issue 5 (12th March 2019) - Stancil, Stephani L.; Pearce, Robin E.; Tyndale, Rachel F.; Kearns, Gregory L.; Vyhlidal, Carrie A.; Leeder, J. Steven; Abdel‐Rahman, Susan
Abstract : Aims: CYP2A6 is a genetically polymorphic enzyme resulting in differential substrate metabolism and health behaviours. Current phenotyping probes for CYP2A6 exhibit limitations related to procurement (deuterated cotinine), toxicity (coumarin), specificity (caffeine) and age‐appropriate administration (nicotine, NIC). In vitro, CYP2A6 selectively forms 2‐hydroxymetronidazole (2HM) from metronidazole (MTZ). The purpose of this study was to evaluate MTZ as a CYP2A6 phenotyping probe drug in healthy adults against the well‐established method of measuring trans‐3‐hydroxycotinine (3HC)/cotinine (COT). Methods: A randomized, cross‐over, pharmacokinetic study was completed in 16 healthy, nonsmoking adults. Separated by a washout period of at least 2 weeks, MTZ 500 mg and NIC gum 2 mg were administered and plasma was sampled over 48 hours and 8 hours, respectively. Correlations of plasma metabolite/parent ratios (2HM/MTZ; 3HC/COT) were assessed by Pearson coefficient. CYP2A6 genotyping was conducted and incorporated as a variable of plasma ratio response. Results: Correlations between the plasma ratio 2HM/MTZ and 3HC/COT were ≥ 0.9 at multiple time points ( P < 0.001), demonstrating a wide window during which 2HM/MTZ can be queried post‐MTZ dose. CYP2A6 genotype had significant impacts on both MTZ and NIC phenotyping ratios with decreased activity predicted phenotypes demonstrating 2HM/MTZ ratios ≤58% and 3HC/COT ratios ≤56% compared with extensive activity predicted phenotypes at all time points examined in the study ( P < 0.05). No adverse events were reported in the MTZ arm while 38% ( n = 6) of participants reported mild adverse events in the NIC arm. Conclusions: Metronidazole via 2HM/MTZ performed well as a novel, safe phenotyping probe for CYP2A6 in healthy adults.